Exploring Online Reading Strategies and Comprehension of Texts for EFL Learners’ Use in 5.0 Society Development Era - Rinantanti, Yulini; Rahayu, Budi; Ibrahim, Muliaty; Faot, Onisimus; Limbong, Sunarlia (STAI Hubbulwathan Duri, 2024)
The rapid growth of online instruction has significantly transformed education, particularly in the 5.0 society development era. This study investigates the online reading strategies and comprehension skills of English as a Foreign Language (EFL) learners, aiming to better understand how students approach online texts and the challenges they encounter. Using a qualitative case study design, fifteen EFL students were selected through purposive sampling. Data were gathered through observations and semi-structured interviews to identify the reading strategies employed by these learners in an online environment. The results revealed that EFL learners used various effective strategies to engage meaningfully with online materials. However, notable differences in reading strategies were observed based on individual preferences, leading to diverse outcomes in comprehension. These variations highlight the challenges some students face in understanding online content, emphasizing the need for more personalized approaches in online reading instruction. The study suggests that while EFL learners can apply appropriate online reading strategies, their effectiveness depends on individual reading preferences and comprehension levels. Consequently, educators should address these differences by designing flexible and adaptable reading lessons. The integration of both basic and more advanced strategies is essential to support all learners in navigating online texts effectively.